2018
DOI: 10.1158/1541-7786.mcr-17-0726
|View full text |Cite
|
Sign up to set email alerts
|

AHNAK Loss in Mice Promotes Type II Pneumocyte Hyperplasia and Lung Tumor Development

Abstract: AHNAK is known to be a tumor suppressor in breast cancer due to its ability to activate the TGFβ signaling pathway. However, the role of AHNAK in lung tumor development and progression remains unknown. Here, the Ahnak gene was disrupted to determine its effect on lung tumorigenesis and the mechanism by which it triggers lung tumor development was investigated. First, AHNAK protein expression was determined to be decreased in human lung adenocarcinomas compared with matched nonneoplastic lung tissues. Then, Ahn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 39 publications
0
16
1
Order By: Relevance
“…It was demonstrated to act as a tumor suppressor in lung and breast cancer and in melanoma. In contrast, an upregulation and involvement in cancer cell migration and invasion in mesothelioma was reported [3640]. Consistent with the latter hypothesis, AHNAK deficient keratinocytes exhibited reduced migration, invasion and metastatic properties [28].…”
Section: Discussionmentioning
confidence: 64%
“…It was demonstrated to act as a tumor suppressor in lung and breast cancer and in melanoma. In contrast, an upregulation and involvement in cancer cell migration and invasion in mesothelioma was reported [3640]. Consistent with the latter hypothesis, AHNAK deficient keratinocytes exhibited reduced migration, invasion and metastatic properties [28].…”
Section: Discussionmentioning
confidence: 64%
“…37 A previous study found that AHNAK expression was significantly reduced in human lung adenocarcinomas compared with matched normal lung tissues, and reduced AHNAK expression enhanced Type II Pneumocyte Hyperplasia and expedited the lung tumor development. 38 AHNAK degradation could maintain the stemness of lung cancer stem-like cells. 39 Consistently, this study showed that AHNAK expression was significantly decreased in NSCLC tissues and cells.…”
Section: Discussionmentioning
confidence: 99%
“…In particular myoferlin is a part of a network promoting muscle growth, since (1) myoferlin knock-out in mice leads to smaller skeletal muscles due to reduced myofiber size [124]; (2) myoferlin enhances promitotic signaling by supporting recycling to the PM of the potent muscle growth stimulator IGF1R and preventing its degradation [125] and (3) myoferlin could possibly control the activity of the tumor suppressor and nuclear protein AHNAK and of ADAM12. Myoferlin and AHNAK interact and both can translocate to the nuclei [57,89,90,127,228,229]. ADAM12, another myoferlin binding protein normally expressed by myoblasts is required for myoblast fusion and contains a metalloproteinase domain that cleaves type IV collagens [230][231][232].…”
Section: Ferlins In Human Diseases: Cancermentioning
confidence: 99%